To Assess The Risk Factors of Non-Communicable Diseases among middle aged people attending OPD’S of selected Hospital Kolar with a view to Develop an Health Education Pamphlet on prevention of Non-Communicable diseases - K Gunasheela; G Vijayalakshmi (Journal of Clinical and Biomedical Sciences)
Background: Non-Communicable Diseases (NCDs) are the major health problems of world, more than two out of three deaths are due to NCDs. More than one in two deaths in India (60%) are because of NCDs. A large proportion of NCDs are preventable if correct information is provided by a health care workers at right time in order to practice a healthy lifestyle which in turn to reduce their risk for NCDs. Objective: To assess the risk-factors of non-communicable disease among middle aged people by using checklist. Methods: Fifty middle aged people were included in the study through purposive sampling technique. Participants were assessed for risk factors of Non-communicable diseases by using modified WHO checklist on risk factors of Non-communicable diseases. Data was analyzed by using Descriptive and Inferential Statistics like mean, percentage, standard deviation and chi-square. Results: Out of fifty people 30% were Smokers and 34% were using non smokable tobacco. 20% were using alcohol, 14% of their blood pressure was raised above 140/90 mm of Hg when measured by health professionals and 22% of them had family history of hypertension, 32% of them were following healthy diet and 76% of them were following unhealthy dietary habit. 70% of the people are performing moderate activity. Conclusion: Study concluded that there were risk factors of non-communicable diseases among middle aged people. Distribution of health education pamphlet to middle aged people will help on preventing of Non-communicable diseases. Keywords: Non-communicable diseases (NCDs), Risk factors, Middle aged people, health education pamphlet, Prevention.